Alma Observations of Young Eruptive Stars: Continuum Disk Sizes and Molecular Outflows - Perez-Marquez, S (IOP Publishing Ltd, 2020)
We present Atacama Large Millimeter/submillimeter Array (ALMA) 1.3 mm observations of four young, eruptive star-disk systems at 0.″4 resolution: two FUors (V582 Aur and V900 Mon), one EXor (UZ Tau E), and one source with an ambiguous FU/EXor classification (GM Cha). The disks around GM Cha, V900 Mon, and UZ Tau E are resolved. These observations increase the sample of FU/EXors observed at subarcsecond resolution by 15%. The disk sizes and masses of FU/EXors objects observed by ALMA so far suggest that FUor disks are more massive than Class 0/I disks in Orion and Class II disks in Lupus of similar size. EXor disks in contrast do not seem to be distinguishable from these two populations. We reach similar conclusions when comparing the FU/EXor sample to the Class I and Class II disks in Ophiuchus. FUor disks around binaries are host to more compact disks than those in single-star systems, similar to noneruptive young disks. We detect a wide-angle outflow around GM Cha in 12CO emission, wider than typical Class I objects and more similar to those found around some FUor objects. We use radiative transfer models to fit the continuum and line data of the well-studied disk around UZ Tau E. The line data are well described by a Keplerian disk, with no evidence of outflow activity (similar to other EXors). The detection of wide-angle outflows in FUors but not in EXors support the current picture in which FUors are more likely to represent an accretion burst in the protostellar phase (Class I), while EXors are smaller accretion events in the protoplanetary (Class II) phase. © 2020. The American Astronomical Society. All rights reserved..